Preparation method of PPS (polyphenylene sulfide) composite membrane for hydrogen production by alkaline electrolysis of water

By mixing the PPS wovens with acid mixing and impregnating the cerium precursor and alkali solution multiple times, a PPS composite film with excellent mechanical properties and high hydrophilicity was prepared, which solved the problem of hydrophilic failure of the existing membrane in a high alkali environment, and improved the hydrogen production efficiency and system stability.

CN119824677APending Publication Date: 2025-04-15XIAMEN SAVINGS ENVIRONMENTAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411933734.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The membranes of existing alkaline electrolytic hydrogen production devices have a fast hydrophilic failure rate in high alkali environments, resulting in low hydrogen production efficiency and unstable system.

Method used

After the PPS wovens were treated with mixed acid solution, the cerium precursor solution and alkali solution were impregnated respectively, and the treatment was repeated at least twice to prepare a PPS composite film with excellent mechanical properties and high hydrophilicity.

Benefits of technology

The hydrophilicity and resistivity of the diaphragm are improved, the conduction performance to hydroxide ions is enhanced, the fall of the hydrophilic layer is delayed, and the stability and hydrogen production efficiency of the diaphragm are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824677A_ABST
    Figure CN119824677A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a PPS composite membrane for hydrogen production from alkaline electrolyzed water, the prepared composite membrane has the advantages of good hydrophilicity, low resistivity, simple preparation and the like, and the preparation method specifically comprises the following steps: step 1, selecting a PPS woven fabric, purging the PPS woven fabric with air, and cutting the PPS woven fabric for later use; 2, hydrogen peroxide, acetic acid, sulfuric acid and water are mixed, a mixed acid solution is prepared, the cut PPS woven fabric is soaked in the mixed acid solution to be treated, and then the PPS woven fabric is cleaned and dried to obtain a modified PPS woven fabric; 3, the modified PPS woven fabric is sequentially soaked in a cerium precursor solution and an alkali solution to be treated and then dried; and 4, repeating the step 3 for at least two times to prepare the PPS composite membrane for hydrogen production by alkaline electrolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen production by alkaline water electrolysis, and in particular relates to a method for preparing a PPS composite membrane for hydrogen production by alkaline water electrolysis. Background Art

[0002] Hydrogen energy is the most ideal secondary energy source. Among the many hydrogen production technologies, alkaline water electrolysis has disadvantages such as low hydrogen production efficiency and poor dynamic response, but it also has advantages such as simple structure and easy operation. As a key device in the alkaline water electrolysis hydrogen production device, the diaphragm mainly plays the role of isolating the hydrogen and oxygen produced by electrolysis and transmitting ions, which directly affects the safety and hydrogen production cost of the alkaline water electrolysis hydrogen production device during operation.

[0003] In the existing technology, there are three generations of commercial alkaline electrolytic diaphragms: asbestos electrolytic diaphragms, polyphenylene sulfide (PPS) woven diaphragms and composite diaphragms. Asbestos diaphragms have been eliminated from the market due to their carcinogenicity. PPS is a new material with excellent acid and alkali resistance, high temperature resistance and structural stability. The woven or non-woven diaphragms prepared with it have been widely studied: Lin Yali et al. treated PPS woven fabrics with concentrated sulfuric acid, which significantly enhanced the hydrophilicity of PPS woven fabrics and reduced the water contact angle from 90° to 0°, but the tensile strength of the modified PPS woven fabrics was significantly reduced. Chinese patent CN119082796A obtains PPS modified filament fiber by modifying PPS fiber with sulfuric acid, hydrogen peroxide and acetic acid, and further prepares modified PPS filament fiber membrane by hot rolling process. The increase of oxygen element in the modified fiber improves the hydrophilicity of the membrane, thereby reducing the surface resistance and energy consumption; and the filament fiber also improves the mechanical strength of the membrane, while optimizing the pores and pore size of the membrane, reducing the hairiness, and ensuring the safety in the hydrogen production process; however, the method of adding hydrophilic functional groups to PPS fiber by chemical modification alone is generally poor in durability and cannot meet the requirements of long-term stable operation of the hydrogen production system. Chinese patent CN115142089A obtains layered double metal hydroxide by in-situ growth method, mixes it in casting solution, and then obtains organic-inorganic composite membrane by solution casting method, which has excellent ion conductivity, but the solution casting method has high process requirements for membrane preparation and is difficult to achieve large-scale industrialization. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing a PPS composite membrane for hydrogen production by alkaline water electrolysis, so as to solve the problems existing in the prior art. The prepared composite membrane has the advantages of good hydrophilicity, low resistivity and simple preparation.

[0005] In order to achieve the above object, the solution of the present invention is: A method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis comprises the following steps: Step 1, select PPS woven fabrics and blow them clean with air, and cut them for later use; Step 2, hydrogen peroxide, acetic acid, sulfuric acid and water are mixed to prepare a mixed acid solution, the cut PPS woven fabric is immersed in the mixed acid solution for treatment, and then washed and dried to obtain a modified PPS woven fabric; Step 3, immersing the modified PPS woven fabric in a cerium precursor solution and an alkaline solution in sequence, and then drying; Step 4: Repeat step 3 at least twice to obtain a PPS composite membrane for producing hydrogen by alkaline water electrolysis.

[0006] In step 1, the weight of the selected PPS woven fabric is 400-600 g / m 2 , dry air permeability is 5~30L / (dm 2 *min), thickness is 0.8~2.0mm.

[0007] In step 2, water is used as a solvent in the mixed acid solution, and the mass concentrations of other components are: 15% to 30% hydrogen peroxide, 25% to 40% acetic acid, and 20% to 50% sulfuric acid.

[0008] In the step 2, the cut PPS woven fabric is treated in the mixed acid solution for 10 to 20 minutes at a temperature of 20 to 40°C.

[0009] In the step 2, the drying temperature is 60-100°C; in the step 3, the drying temperature is 150-200°C.

[0010] In the step 3, the cerium precursor is one of cerium nitrate hexahydrate, ammonium cerium nitrate, cerium chloride, and cerium acetate.

[0011] In step 3, the Ce in the cerium precursor solution 4+ / Ce 3+ Concentration: 0.1~2M.

[0012] In step 3, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0013] In step 3, the concentration of the alkaline solution is 2-15M.

[0014] In the step 3, the modified PPS woven fabric is first immersed in the cerium precursor solution until adsorption is saturated, and then immersed in the alkaline solution for 5 minutes.

[0015] After adopting the above technical solution, the present invention has the following technical effects: ①The reaction process is relatively mild, the equipment requirements are simple, and it is easy to industrialize and mass produce; ② Mixed acid modification introduces a large number of sulfonic acid, sulfone and sulfoxide structures into PPS woven fabrics, which strengthens the hydrophilic properties of PPS woven fabrics and provides abundant attachment sites for cerium oxide / hydroxide, thus avoiding the shedding of the hydrophilic layer and improving the stability of the diaphragm; ③ Through the impregnation treatment, cerium oxide / hydroxide is uniformly grown in situ on the modified PPS woven fabric, optimizing the pore structure of the diaphragm and improving the air tightness of the diaphragm; ④ The addition of cerium oxide / hydroxide increases the hydroxyl ion conductivity of the membrane; ⑤ The final PPS composite membrane has the advantages of excellent mechanical properties, good hydrophilicity, low resistivity and stable performance in a high alkaline environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The figure is a schematic diagram of the preparation process of a specific embodiment of the present invention. DETAILED DESCRIPTION

[0017] The present invention is further described below in conjunction with specific implementation methods, but the protection scope of the present invention should not be limited to the following embodiments. Some non-essential adjustments and modifications to the present invention based on the above invention content still fall within the protection scope of the present invention.

[0018] First, according to Figure 1 , carry out the preparation of Example 1-5: Example 1 Step 1: Select a weight of 450g / m 2 , thickness 1.0mm, air permeability 9.8L / (dm 2 *min) of commercial PPS woven fabric products, cleaned with air and cut for use; Step 2, 15% mass concentration of hydrogen peroxide, 25% mass concentration of acetic acid and 35% mass concentration of sulfuric acid are mixed to prepare a mixed acid solution, the above PPS woven fabric sample is taken, immersed in the mixed acid solution at 26° C. for 20 minutes, washed and dried at 100° C. to prepare a modified PPS woven fabric sample; Step 3, immersing the modified PPS woven fabric sample in a 1.0M cerium nitrate hexahydrate solution for 1 min until adsorption saturation, moving it to a 15M sodium hydroxide solution using a fixture and immersing it for 5 min, and then drying it at 180°C; Step 4: Repeat the above step 3 twice to obtain a PPS composite film.

[0019] Example 2 Step 1: Select the weight of 500g / m 2 , thickness 1.0mm, air permeability 7.5L / (dm 2*min) of commercial PPS woven fabric products, cleaned with air and cut for use; Step 2, 15% mass concentration of hydrogen peroxide, 25% mass concentration of acetic acid and 35% mass concentration of sulfuric acid are mixed to prepare a mixed acid solution, the above PPS woven fabric sample is taken, immersed in the mixed acid solution at 27° C. for 20 minutes, washed and dried at 100° C. to prepare a modified PPS woven fabric sample; Step 3, immersing the modified PPS woven fabric sample in a 1.0M cerium nitrate solution for 1 min until adsorption saturation, moving it to a 10M sodium hydroxide solution using a clamp and immersing it for 5 min, and then drying it at 180°C; Step 4: Repeat the above step 3 twice to obtain a PPS composite film.

[0020] Example 3 Step 1: Select a weight of 450g / m 2 , thickness 1.0mm, air permeability 9.8L / (dm 2 *min) of commercial PPS woven fabric products, cleaned with air and cut for use; Step 2, 20% mass concentration of hydrogen peroxide, 30% mass concentration of acetic acid and 35% mass concentration of sulfuric acid are mixed to prepare a mixed acid solution, the above PPS woven fabric sample is taken, immersed in the mixed acid solution at 30° C. for 20 minutes, washed and dried at 80° C. to prepare a modified PPS woven fabric sample; Step 3, immersing the modified PPS woven fabric sample in a 1.0M cerium ammonium nitrate solution for 1 min until adsorption saturation, moving it to a 15M sodium hydroxide solution using a clamp and immersing it for 5 min, and then drying it at 200°C; Step 4: Repeat the above step 3 once to obtain a PPS composite film.

[0021] Example 4 Step 1: Select a weight of 450g / m 2 , thickness 1.0mm, air permeability 9.8L / (dm 2 *min) of commercial PPS woven fabric products, cleaned with air and cut for use; Step 2, 15% mass concentration of hydrogen peroxide, 25% mass concentration of acetic acid and 35% mass concentration of sulfuric acid are mixed to prepare a mixed acid solution, the above PPS woven fabric sample is taken, immersed in the mixed acid solution at 30° C. for 15 minutes, washed and dried at 80° C. to prepare a modified PPS woven fabric sample; Step 3, immersing the modified PPS woven fabric sample in a 1.0M cerium nitrate solution for 1 min until adsorption saturation, moving it to a 15M sodium hydroxide solution using a clamp and immersing it for 5 min, and then drying it at 180°C; Step 4: Repeat the above step 3 twice to obtain a PPS composite film.

[0022] Example 5 Step 1: Select a weight of 450g / m 2 , thickness 1.0mm, air permeability 9.8L / (dm 2 *min) of commercial PPS woven fabric products, cleaned with air and cut for use; Step 2, 20% mass concentration of hydrogen peroxide, 30% mass concentration of acetic acid and 35% mass concentration of sulfuric acid are mixed to prepare a mixed acid solution, the above PPS woven fabric sample is taken, immersed in the mixed acid solution at 25° C. for 30 minutes, washed and dried at 100° C. to prepare a modified PPS woven fabric sample; Step 3, immersing the modified PPS woven fabric sample in a 0.5M cerium ammonium nitrate solution for 1 min until adsorption saturation, moving it to a 10M sodium hydroxide solution using a clamp and immersing it for 5 min, and then drying it at 200°C; Step 4: Repeat the above step 3 twice to obtain a PPS composite film.

[0023] Secondly, the preparations of Comparative Examples 1-3 were carried out respectively: Comparative Example 1 Select weight 500g / m 2 , thickness 1.0mm, air permeability 9.8L / (dm 2 *min) of commercial PPS non-woven felt products, which are cleaned by air blowing and cut into PPS composite films.

[0024] Comparative Example 2 Step 1: Select a weight of 450g / m 2 , thickness 1.0mm, air permeability 9.8L / (dm 2 *min) of commercial PPS woven fabric products, cleaned with air and cut for use; Step 2, immersing the PPS woven fabric sample in a 1.0M cerium nitrate solution for 1 min until adsorption saturation, moving it to a 15M sodium hydroxide solution using a clamp and immersing it for 5 min, and then drying it at 180°C; Step 3: Repeat the above step 2 twice to obtain a PPS composite film.

[0025] Comparative Example 3 Step 1: Select a weight of 450g / m 2 , thickness 1.0mm, air permeability 9.8L / (dm 2 *min) of commercial PPS woven fabric products, cleaned with air and cut for use; Step 2: 20% by mass concentration of hydrogen peroxide, 30% by mass concentration of acetic acid and 35% by mass concentration of sulfuric acid are mixed to prepare a mixed acid solution, the above-mentioned PPS woven fabric sample is taken, immersed in the mixed acid solution at 32° C. for 15 minutes, washed and dried at 80° C. to prepare a PPS composite film.

[0026] The test standards during the test are as follows: (1) The water absorption time is measured according to the provisions of the national standard GB / T 21665-2018. The durable water absorption time is the membrane immersed in a 30% mass concentration KOH solution for 20 days, and then tested after cleaning and drying; (2) The alkali loss rate is measured according to the provisions of the electronic industry standard SJ / T 10171-2016; (3) The surface resistance is measured according to the provisions of the national electronic industry standard SJ-T 10171-2016; (4) The tensile strength is measured according to the provisions of the national standard GB / T 6719-2009; (5) The bubble point pressure is assembled according to the national building materials industry standard JC / T 211-2009 and measured in accordance with the regulations.

[0027] According to the above test standards, the data of Examples 1-5 and Comparative Examples 1-3 are measured as follows:

[0028] According to the above tests and results, we can see that: Mixed acid modification can make PPS fabrics better bond with cerium oxide / hydroxide, greatly delaying the failure rate of hydrophilicity of the diaphragm in alkaline environment; and the addition of cerium oxide / hydroxide can significantly increase the bubble point pressure of the diaphragm while ensuring the hydrophilicity of the diaphragm, providing guarantee for the stable operation of the hydrogen production system.

[0029] The above embodiments and drawings do not limit the product form and style of the present invention. Any appropriate changes or modifications made by ordinary technicians in the relevant technical field should be deemed to be within the patent scope of the present invention.

Claims

1. A method for preparing a PPS composite membrane for hydrogen production by alkaline water electrolysis, characterized in that The following steps are involved: Step 1, select PPS woven fabrics and blow them clean with air, and cut them for later use; Step 2, hydrogen peroxide, acetic acid, sulfuric acid and water are mixed to prepare a mixed acid solution, the cut PPS woven fabric is immersed in the mixed acid solution for treatment, and then washed and dried to obtain a modified PPS woven fabric; Step 3, immersing the modified PPS woven fabric in a cerium precursor solution and an alkaline solution in sequence, and then drying; Step 4: Repeat step 3 at least twice to obtain a PPS composite membrane for producing hydrogen by alkaline water electrolysis.

2. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In step 1, the weight of the selected PPS woven fabric is 400-600 g / m 2 , dry air permeability is 5~30L / (dm 2 *min), thickness is 0.8~2.0mm.

3. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis as claimed in claim 1, characterized in that: In step 2, water is used as a solvent in the mixed acid solution, and the mass concentrations of other components are: 15% to 30% hydrogen peroxide, 25% to 40% acetic acid, and 20% to 50% sulfuric acid.

4. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In the step 2, the cut PPS woven fabric is treated in the mixed acid solution for 10 to 20 minutes at a temperature of 20 to 40°C.

5. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In the step 2, the drying temperature is 60-100°C; in the step 3, the drying temperature is 150-200°C.

6. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In the step 3, the cerium precursor is one of cerium nitrate hexahydrate, ammonium cerium nitrate, cerium chloride, and cerium acetate.

7. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In step 3, the Ce in the cerium precursor solution 4+ / Ce 3+ Concentration: 0.1~2M.

8. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In step 3, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

9. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In step 3, the concentration of the alkaline solution is 2-15M.

10. The method for preparing a PPS composite membrane for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In the step 3, the modified PPS woven fabric is first immersed in the cerium precursor solution until adsorption is saturated, and then immersed in the alkaline solution for 5 minutes.

Citation Information

Patent Citations

  • Preparation method of organic-inorganic composite membrane for hydrogen production by alkaline electrolysis of water

    CN115142089A

  • Preparation method of modified polyphenylene sulfide filament fiber diaphragm for alkaline water electrolysis hydrogen production device

    CN119082796A